INDONESIA’S NATIONAL NEWS TRENDS ON THE RICE IMPORT POLICY: A CONTENT ANALYSIS - Dasad Latif; Ruslan Ramli (Indonesia Social Justice Network (ISJN), 2020)
This research discusses the rice import policy of the government of Indonesia in 2018. At the time more than two state institutions differ to see the national rice stock. They are the official state institutions; Central Bureau of Statistic, Ministry of Trade, and Ministry of Agriculture. The National Logistics Agency (Bulog) as state institution which responsibility to the national rice affair of Indonesia is confused to run the policy. Then, the policy reaps polemic, pros, and cons points of view. The pros argue that rice stocks are getting less while the cons argue that rice stocks are available due to harvest. This research aims to explain the trends and alignment of tempo.co and kompas.com toward the policy of rice import taken by the government. The method uses a descriptive-quantitative approach by applying the content analysis technique. It divides of some categories. The result shows that the news tendency of tempo.co tends to apply war journalism, while kompas.com tends to apply peace journalism. For news’ source category, tempo.co and kompas.com empower their reporters in creating a news. They both take a side to the policy for rejecting rice import to Indonesia.